Sustained very low disease activity and remission in psoriatic arthritis patients - Lubrano, E; Perrotta, F; Scriffignano, S; Coates, L; Helliwell, P (Springer, 2019)
Introduction: Sustained remission should be considered the main therapeutic target in psoriatic arthritis (PsA). Very low disease activity (VLDA) and a DAPSA score ≤ 4 are the most commonly used criteria. The aim of the present study was to evaluate the rate of sustained remission in a group of PsA patients followed in a real-life setting.